Design and characterization of a novel braided biodegradable double‐J ureteral stent. (25th April 2022) - Cui, Haipo; Zhang, Kui; Gao, Chenguang; Kang, Yahong; Jiang, Hongyan
Abstract: Ureteral stents in current clinical use are non‐degradable and have a large degree of curling at the ends. This end curling can cause discomfort to patients as well as renal or bladder irritation. In this study, a braided degradable ureteral stent was designed and characterized to eliminate these problems. Eight‐, 12‐, and 16‐strand poly(lactide‐co‐ε‐ caprolactone) (PLCL) monofilament‐braided degradable ureteral stents were prepared, and their tensile performance, radial support performance, in vitro degradation, fixation performance, bending resistance performance, and drainage performance were tested. Compared with the commonly used polyurethane (PU) stent, the tensile strengths of the three types of PLCL stents were higher, with the 12‐strand monofilament‐braided stent exhibiting the highest tensile strength (~508.06 MPa). In terms of radial support, the three PLCL stents meet clinical requirements. After repeated crimping‐rebounding of the braided stent, the support force recovery rate of the 12‐strand monofilament‐braided stent was the best, reaching 92%. In vitro degradation results showed that the 12‐strand stent still maintained good radial support after 8 weeks. The fixation strength of a 12‐strand monofilament‐braided stent with a single loop on the J‐shaped end meets clinical requirements. Even after repeated bending, the 12‐strand monofilament‐braided stent can maintain the stability of the structure with excellent drainage performance.